The Vertical Rectus Abdominis Myocutaneous Flap for Complex Abdominal Wall Reconstruction on a Relapse Case of Monophasic Synovial Sarcoma - Alfadz Kholifah Akbar; Muhammad Pratama Mandala Putra; Denny Irwansyah (Asian Journal of Health Research, 2023)
Introduction: Vertical Rectus Abdominis Myocutaneous (VRAM) flap is a chosen method for a large wound closure instead of Anterolateral Thigh (ALT) flap. Both versatile and highly vascularized flaps share almost similar advantages for large wound closure. In our case, the site and size of the wound are the points of consideration. Case Presentation: A 16-year-old girl with a chief complaint of a large progressive lower abdominal mass enlarged since January 2021 that has grown back from the same site. Abdominal CT-Scan shows a tumor in the right lower abdomen infiltrated to the pelvic cavity and spanning from the lower abdominal area all the way to the groin area. Histopathology interpretation suggests a Monophasic Synovial Sarcoma. The patient underwent a second tumor resection with VRAM flap as the wound closure. The benefits of this versatile flap are excellent dead space obliteration and low Surgical Site Occurrence (SSO’s). Conclusion: As postulated in many studies VRAM flap is an excellent flap for a CAWR procedure. The expected SSO’s is non-existence during the postoperative follow-up